2020
DOI: 10.1038/s41598-020-75663-9
|View full text |Cite
|
Sign up to set email alerts
|

A sciaenid swim bladder with long skinny fingers produces sound with an unusual frequency spectrum

Abstract: Swim bladders in sciaenid fishes function in hearing in some and sound production in almost all species. Sciaenid swim bladders vary from simple carrot-shaped to two-chambered to possessing various diverticula. Diverticula that terminate close to the ears improve hearing. Other unusual diverticula heading in a caudal direction have not been studied. The fresh-water Asian species Boesemania microlepis has an unusual swim bladder with a slightly restricted anterior region and 6 long-slender caudally-directed div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Several studies showed that Atlantic Croaker often produced a "knock" voice when they interacted with each other with an average sound duration of 97 msec (SD = 56, 95% C.I. = 88-106) and correlated positively with Atlantic Croaker density [9]. Johnius macrorhynus makes a sound with a frequency of up to 5 kHz, with two peaks around 1 and 2 kHz, the first being the dominant frequency.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies showed that Atlantic Croaker often produced a "knock" voice when they interacted with each other with an average sound duration of 97 msec (SD = 56, 95% C.I. = 88-106) and correlated positively with Atlantic Croaker density [9]. Johnius macrorhynus makes a sound with a frequency of up to 5 kHz, with two peaks around 1 and 2 kHz, the first being the dominant frequency.…”
Section: Resultsmentioning
confidence: 99%